A lemma on limits of analytic sets - Rosas, Rudy (Pontificia Universidad Católica del Perú, 2005)
This paper is a small remark on the analyticity of a limit of analytic sets in a particular case: when the sets are complex discs.
Keywords: Analytic Sets; Limits Of Sets; Complex Discs; https://purl.org/pe-repo/ocde/ford#1.01.00